The Effect of Macroeconomic Variables on Stock Returns of The Jakarta Islamic Index: A Panel Vector Error Correction Model Approach - Budi, Bagus Setiyo; Faizin, Moh. (Institut Agama Islam Negeri Ponorogo, 2024)
Introduction: This study was conducted because there were differences in stock return trends in JII during 2016-2018, where stock return movements simultaneously decreased, but different conditions occurred in 2019-2022, where trend returns experienced different conditions between companies. This was caused by the domino effect of the Covid-19 Pandemic, which resulted in changes in Indonesia's BI Rate and Inflation. Thus, this study aims to analyze the long and short-term effects of BI Rate and Inflation on changes in the return of company shares in JII. Research Methods: This study uses the Panel Vector Error Correction Model (VECM) method, secondary data in the form of a Panel of Stock Return of 4 companies, BI Rate and Inflation during 2016-2022. Results: The long and short-term results in the previous two and three-quarters of the BI Rate were significantly positive for stock returns. While in the long and short term, inflation was significantly negative for stock returns. Conclusion: The research found that the BI Rate does not always negatively affect return. When the BI Rate increases, it gives investors confidence that the value of their investment is protected from depreciation. This can create a positive environment for the stock market so that it has an impact on rising stock prices.